If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1n = 14 Solving 7 + -1n = 14 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1n = 14 + -7 Combine like terms: 7 + -7 = 0 0 + -1n = 14 + -7 -1n = 14 + -7 Combine like terms: 14 + -7 = 7 -1n = 7 Divide each side by '-1'. n = -7 Simplifying n = -7
| y=-4/7-4 | | -7x+5(x+6)=26 | | -2v+6(v-6)=-16 | | -16=7y+3(y+8) | | 5.3=-3v+24.5 | | -1.1+y/4=-13.9 | | y=-9/4+9 | | 8x+7=(x-8) | | (w-5)(2w-5)= | | 3(x+2)/4=2x-4 | | 12=4+u/20.48 | | 8.1=7u-3.1 | | w/5+4.1=-8.4 | | -12t^4+16t^3+3t^2= | | 4+u/3=7 | | 17=2y+5 | | 90x^3+33x^2+3x= | | 10=4+y/2 | | 10=4+y-2 | | 0=10x^2+28x-174 | | 156=-y+64 | | 60x^3+35x^2+5= | | 207-x=88 | | -w+199=147 | | w/9=-39 | | 2x^2-24x-3955977=0 | | -56=-v/6 | | 10x-10=6x-2 | | H-(41)=-6 | | -2v=-17 | | (-7x^5+12x^4+7x^3+9x)-(-3x^5-4x^4-11x^2+9x)= | | 5.12=w/2 |